Clinical application and drug resistance mechanism of gemcitabine - Zhang, Xuanrui; Qi, Bing; Chen, Jing (Frontiers in Cell and Developmental Biology, 2025)
Gemcitabine, as a nucleoside analog, exerts a broad-spectrum antitumor effect by interfering with DNA synthesis, but its clinical application is limited by drug resistance. The drug resistance mechanism involves metabolic abnormalities (such as downregulation of deoxycytidine kinase (dCK), nucleoside transporter hENT1 deficiency), enhanced DNA repair (overexpression of ribonucleotide reductase ribonucleotide reductase catalytic subunit M1 (RRM1)/ribonucleotide reductase catalytic subunit M2 (RRM2), and tumor microenvironment remodeling (such as secretion of immunosuppressive factors by CAFs). This article systematically reviews the drug resistance mechanism of gemcitabine and explores the breakthrough direction of new drug delivery systems (liposomes, albumin nanoparticles) and combination therapy strategies (targeted drugs, immune checkpoint inhibitors). In addition, cutting-edge technologies such as single-cell sequencing and artificial intelligence drug sensitivity prediction provide a new paradigm for precision treatment. In the future, it is necessary to build a “prevention-monitoring-intervention” full-chain management system through dynamic monitoring of multi-omics biomarkers (such as circulating tumor DNA tracking RRM2 amplification) and coordinated intervention of traditional Chinese and Western medicine (such as curcumin reversing drug resistance).